My dad is awesome - Butterworth, Nick. (Cambridge, Mass. : Candlewick Press, 2003)
A young boy extols the virtues of his father.
"First published in Great Britain in 1989 by Walker Books Ltd., London"--P. facing t.p.
1.2.
1.2
K-3
Keywords: Fathers and sons -- Juvenile fiction; Fathers -- Juvenile fiction; Fathers and sons -- Fiction; Fathers -- Fiction; Father-son relationship -- Fiction; Fathers -- Fiction